30 years of Black or White: intercultural discussions through the alasa kanyas of the Indian dance Odissi in the music video of Michael Jackson (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
In this article we propose to reflect on the theme of interculturality foreshadowed in the music video Black or White, by Michael Jackson, in 1991, putting it in perspective with intercultural discussions in the context of the scene arts today. Despite the “magazine” format adopted by the video clip, in its successive dance scenes from different cultures, we note that the choices related to Odissi dance all have well-defined purposes and interlocution with the lyrics of the song, therefore, justifying a detailed analysis of these choices, especially of the alasa kanyas. This perception leads us to argue in favor of the pioneering spirit of this music video that, in the 1990s, foreshadowed the debate on interculturality, movement of the performing arts that expanded from the 1970s onwards, and equity currently on agenda in the broader social sphere, as well as possible differences in readings between generations.
Keywords: Odissi; Interculturality; Pop Culture; Intergenerationality